KAJIAN FILOLOGI DAN CARA MENDIDIK DALAM NASKAH DHEDHASARANING WEWATEKANIPUN MANUNGSA - Bunga Candra Nur Arini; Endang Nurhayati (Fakultas Sastra Universitas Negeri Malang, 2020)
PHILOLOGICAL STUDY AND STUDENT EDUCATION in DHEDHASARANING WEWATEKANIPUN MANUNGSA TEXTAbstract: This research aims to reveal the steps of philology research on the Dhedhasaraning Wewatekanipun Manungsa text and reveal how the text can be used by teachers to educate students with different personalities, so learning can be more effective. This study is qualitative research utilizing philological approach. The data were analyzed using content analysis techniques, starting from unitization, sampling, recording data, describing data, making inferences, and analyzing data. The results of this study include manuscript inventory, manuscript description, transliteration, and editing of the Dhedhasaraning Wewatekanipun Manungsa manuscript. The study also discusses the manuscript proposes ways to educate students based on their personalities, for example, bingahan personality students are educated with an enthusiastic approach, kerasan personality students are educated in a decisive style, sedhihan personality students are educated with understanding and encouragement, while sarehan personality students are educated patiently. The Dhedhasaring Wewatakipun Manungsa text contains values that could be a guide for teachers to educate their student according to their personalities, make teaching and learning more effective, and developing students’ characters.Keywords: Philology, Dhedhasaraning Wewatekanipun Manungsa, Javanese manuscripts, EducationKAJIAN FILOLOGI DAN CARA MENDIDIK DALAM NASKAH DHEDHASARANING WEWATEKANIPUN MANUNGSAAbstrak: Penelitian ini bertujuan untuk menjelaskan langkah-langkah penelitian filologi terhadap naskah Dhedhasaraning Wewatekanipun Manungsa dan cara mendidik siswa supaya naskah dapat digunakan oleh guru sebagai panduan mendidik siswa yang memiliki kepribadian yang berbeda-beda sehingga dapat tercipta keefektifan belajar. Metode yang digunakan pada penelitian ini adalah kualitatif dengan pendekatan teori filologi. Analisis data menggunakan teknik analisis isi yaitu unitisasi, sampling, mencatat data, menjabarkan data, menarik inferensi dan menganalisis. Hasil penelitian ini adalah inventarisasi naskah, deskripsi naskah, transliterasi, dan suntingan dengan aparat kritik dari naskah Dhedhasaraning Wewatekanipun Manungsa. Dalam penelitian dibahas bagaimana naskah tersebut menyebutkan cara mendidik siswa berdasarkan kepribadiannya yaitu kepribadian bingahan dididik dengan cara yang semangat, kepribadian kerasan dididik dengan cara yang tegas, kepribadian sedhihan dididik dengan pengertian dan penyemangat, dan kepribadian sarehan dididik dengan sabar. Ilmu di dalam teks Dhedhasaraning Wewatekanipun Manungsa bisa menjadi panduan guru untuk mendidik siswa sesuai dengan kepribadiannya sehingga dapat meningkatkan kualitas pembelajaran menjadi lebih efektif dan membentuk karakter siswa menjadi lebih baik.Kata kunci: Filologi, Dhedhasaraning Wewatekanipun Manungsa, Manuskrip Jawa, Pendidikan siswa Permalink/DOI: dx.doi.org/10.17977/um015v48i22020p103